Analysis of Semantics in Literature "The Romance of A Busy Broker" Concentrating on Sentence, Utterance and Presupposition - Hasy, Aulia Dagna (Jejak digital: Jurnal Ilmiah Multidisiplin, 2025)
This article examines how sentence structure, utterance, and presupposition contribute to the meaning of "The Romance of a Busy Broker" within a structure of semantic theory. Each semantics theory in this article derived the contextual story, characters emotion and what behind narrative told, all of those things would elaborate as simple and unique cover for making the readers understood about many things was discussed through the entire content of the article. The aims was concentrated through this research point is all about finding exactly extrinsic relevance between the topics was talked and the data which the research was found. The article offers a qualitative method that involves arranged a data list, organized it properly and all the data was analyzed, included insights from several linguistic philosophers. The result of data finding was dragged to diversified the subject of sentence, utterance and presupposition between the author’s key ideas and philosophers belief in linguistic conceptual. The author analytical about this story based on what famous person in linguistic said, and also modified each type of analysis using correct sciencetific article guided. In spite of that, the final discussion was found with qualitative methods depends on Cresswell’s argument and completed it with another author’s ideas.